2013
DOI: 10.1128/mbio.00255-13
|View full text |Cite
|
Sign up to set email alerts
|

Human Innate Immunity to Toxoplasma gondii Is Mediated by Host Caspase-1 and ASC and Parasite GRA15

Abstract: Interleukin-1β (IL-1β) functions as a key regulator of inflammation and innate immunity. The protozoan parasite Toxoplasma gondii actively infects human blood monocytes and induces the production of IL-1β; however, the host and parasite factors that mediate IL-1β production during T. gondii infection are poorly understood. We report that T. gondii induces IL-1β transcript, processing/cleavage, and release from infected primary human monocytes and THP-1 cells. Treating monocytes with the caspase-1 inhibitor Ac-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(136 citation statements)
references
References 56 publications
6
124
0
4
Order By: Relevance
“…The idea of a link between the inflammasome and human toxoplasmosis was further supported by data showing that IL-1␤ expression in human monocytes was dependent on caspase-1 and ASC, which is an adaptor protein that mediates caspase-1 binding to either the NLRP1/caspase-5 or the NLRP3/CARDB inflammasomes (64,68). IL-1␤ was significantly upregulated by type II strain parasites (i.e., the Pru strain), and this polymorphic effect was dependent on GRA15, which mostly likely upregulates expression of IL-1␤ by virtue of its ability to activate NF-B (68). Infection of human monocytes with type I, II, or III Toxoplasma tachyzoites did not result in rapid cell death, as the assays in the studies cited above were carried out at 24 and 36 h (67, 68), suggesting that under those conditions, inflammasome activation was not triggering pyroptosis.…”
Section: The Inflammasomementioning
confidence: 66%
See 1 more Smart Citation
“…The idea of a link between the inflammasome and human toxoplasmosis was further supported by data showing that IL-1␤ expression in human monocytes was dependent on caspase-1 and ASC, which is an adaptor protein that mediates caspase-1 binding to either the NLRP1/caspase-5 or the NLRP3/CARDB inflammasomes (64,68). IL-1␤ was significantly upregulated by type II strain parasites (i.e., the Pru strain), and this polymorphic effect was dependent on GRA15, which mostly likely upregulates expression of IL-1␤ by virtue of its ability to activate NF-B (68). Infection of human monocytes with type I, II, or III Toxoplasma tachyzoites did not result in rapid cell death, as the assays in the studies cited above were carried out at 24 and 36 h (67, 68), suggesting that under those conditions, inflammasome activation was not triggering pyroptosis.…”
Section: The Inflammasomementioning
confidence: 66%
“…Moreover, parasite growth was enhanced whereas host cell viability and IL-1␤ and IL-18 expression were reduced in monocytes engineered to express decreased levels of NLRP1 protein (67,68). The idea of a link between the inflammasome and human toxoplasmosis was further supported by data showing that IL-1␤ expression in human monocytes was dependent on caspase-1 and ASC, which is an adaptor protein that mediates caspase-1 binding to either the NLRP1/caspase-5 or the NLRP3/CARDB inflammasomes (64,68). IL-1␤ was significantly upregulated by type II strain parasites (i.e., the Pru strain), and this polymorphic effect was dependent on GRA15, which mostly likely upregulates expression of IL-1␤ by virtue of its ability to activate NF-B (68).…”
Section: The Inflammasomementioning
confidence: 99%
“…A concept that is now gaining acceptance is that induction of proinflammatory cytokines essential for in vivo control of acute Toxoplasma infection involves intracellular signaling from endosomal and cytoplasmic pattern recognition receptors (PRRs) (22)(23)(24)(25)(26). Interestingly, the inflammatory cytokines IL-12 and IL-1β are both induced differentially by avirulent, but not virulent, Toxoplasma strains (9,27,28), presumably through intracellular activation of TLRs and other PRRs. However, how these intracellular PRRs are activated during live Toxoplasma infection is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Our data partially correlate with those of previous studies showing that GRA7-induced innate immune responses were MyD88 dependent but not TLR dependent, suggesting that other members of the TLR family or pattern recognition receptors are involved. A recent study showed that the recognition of T. gondii through the activation of the intracellular sensor NLRP1 and NLRP3 inflammasomes induced cell death and the production of IL-1␤ in in vitro and in vivo experiments with mouse and rat cells (32)(33)(34). Furthermore, T. gondii has been reported to be a novel activator of the NLRP1 and NLRP3 inflammasomes in vivo and a role for these sensors in host resistance to toxoplasmosis has been established (34).…”
Section: Discussionmentioning
confidence: 99%